The Decentralization of Power and Institutional Adaptations: Decentralized Land Reform in Kayunga, Uganda - Brunton, Kathryn Anne (Université d'Ottawa / University of Ottawa, 2015)
While many African governments have made legislative changes to the formal economic institution of land law in order to strengthen land tenure security, very few have seen these changes take hold (Bruce & Knox, 2009). This thesis demonstrates that Uganda is no exception. In exploring the interactions between the formal, informal, political, economic and social institutions which influence land tenure behaviour in Uganda, and how decentralization impacts this institutional structure, this thesis offers a first step in understanding how state-led land reforms can be undercut at the local level, causing unintended outcomes. From reinforcing the legitimacy of informal customary tenure systems to fostering inter-ethnic competition, the District of Kayunga demonstrates how Uganda’s 1998 Land Reform has created unexpected impacts that continue to impede its implementation. It also offers ideas on how failed institutional adaptations may impact local perceptions of land tenure security. This thesis also investigates and pushes the boundaries of New Institutional Economic (NIE) theory. It explores how decentralization within a formal economic institution can influence informal social and political institutions to create complex and ever evolving incentive structures. It also examines the role of organizations and individuals in an effort to understand the intersection between these two categories of actors and the institutional structure. Fluid interactions whereby organizations and individuals are incentivized by institutions, but also resist and adapt to institutional change, demonstrate the added complexity of organization-institution interdependency within the NIE framework.
Keywords: Land Tenure; Uganda; Resistance; Institutions